The Effect of Profitability Ratio, Liquidity, Ratio and Leverage Ratio to Financial Distress (Studies at Textile and Garment Companies Listed on the Indonesia Stock Exchange 2012- 2016) - Octavia, Evi; Nur Aidina, Erdiana (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The paper aims to investigate the impact of profitability ratio, liquidity ratio, and leverage ratio toward financial distress in textile and garment companies listed on the Indonesia Stock. Design/Methodology/approach: A survey is carried out on 18 textile and garment companies listed on the Indonesia Stock Exchange. through the use of financial statements. Finding: The results of this research prove that the partial fundamentals by using ROA, CR, and DER effect financial distress. Research limitation/implication: The paper focused on the textile and garment companies listed on the Indonesia Stock Exchange. Practical implication: the result provides insights to the textile and garment companies and other organizations of similar nature about the occurrence of financial distress due to an increase in the cost of imported raw materials for fabrics. Originality/value : This paper is perhaps one of the first investigate in the profitability ratio, liquidity ratio, and leverage ratio in the Textile and Garment Companies using a comprehensive set of indicators in investigating influence on financial distress